Reducing the colonial footprint through tutorials: A South African perspective on the decolonisation of education - Hassan, S. L. (South African Journal of Higher Education, 2022)
This article reports on how tutorials are employed as an instrument for the decolonisation of higher education and the promotion of inclusivity. The study was underpinned by activity theory and Bourdieu’s social field theory. Since 2015, students have embarked on nationwide protests against a colonised higher education system that they lament also makes them feel unwelcome and alienated. They have demanded that tertiary institutions be inclusive, address social justice and apply decolonisation. The study reported in this article demonstrated that the tutorial field provided a nurturing space where black tutees were made to feel comfortable on account of the tutors’ symbolic capital and habitus which they could relate to. It is argued here that pedagogical tools such as the application of tutees’ mother-tongue (an example of decolonisation) and the use of group work has the potential to help integrate black tutees into academia. One needs to be cautious, however, that groups which are linguistically similar could be regarded as exclusive.